(untitled) (International Journal of Medical and Surgical Sciences, 2020)
Countless studies carried out by different health areas demonstrate the benefits of exclusive breastfeeding (BF) and the harmonious growth of craniofacial structures for the proper subsequent development of oral functions such as breathing, swallowing and speech. Early intervention by the professional in speech therapy in Intensive Care Units (ICU) shows undeniable benefits as it promotes self-efficacy in the mother, breastfeeding and with it, the reduction of comorbidities in the baby, as well as the reduction of time for the implementation of the oral route. It is important to highlight the importance for the speech pathologist to have validated instruments that allow timely diagnoses and therefore effective treatments. This research is descriptive, with a mixed methodology and non-experimental design; Since it was oriented towards the verification of the validity of the content (external) of the EFIN Comprehensive Speech Therapy Assessment Protocol of the Newborn, also determining its relevance, as it is used as a guiding instrument within the role of the speech therapist in breastfeeding. For validity purposes in terms of sufficiency, relevance and clarity, the validation is carried out through the judgment of experts, with a panel made up of professionals from different Latin American countries, including Colombia, Peru, Chile, Brazil and Argentina, obtaining strong validity of the entire protocol, with a validity coefficient according to Aiken’s V statistical coefficient greater than 0.81. To measure the usefulness of the EFIN instrument in the approach to breastfeeding, a Likert-type survey is carried out observing homogeneous absolute frequencies that allowed us to see the instrument as a very useful tool, not only for breastfeeding but for all areas of neonatology in which the speech therapist participates. Keywords: Stomatognathic functions; communication; neonates; breastfeeding; speech therapy.